2020
DOI: 10.1007/s12250-020-00265-8
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cytokine Elevation, Moderate CD4+ T Cell Response and Abundant Antibody Production in Children with COVID-19

Abstract: Children with Coronavirus Disease 2019 (COVID-19) were reported to show milder symptoms and better prognosis than their adult counterparts, but the difference of immune response against SARS-CoV-2 between children and adults hasn't been reported. Therefore we initiated this study to figure out the features of immune response in children with COVID-19. Sera and whole blood cells from 19 children with COVID-19 during different phases after disease onset were collected. The cytokine concentrations, SARS-CoV-2 S-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 30 publications
7
52
1
Order By: Relevance
“…A role for Th2 cell-type responses in severe COVID-19 is still unclear ( 48 ). An increased Th2 response was described as beneficial in children with COVID-19, due to its potential to reduce exaggerated inflammation ( 49 ). However, we observed that severe COVID-19 patients display strongly up-regulated IL-4 production in both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A role for Th2 cell-type responses in severe COVID-19 is still unclear ( 48 ). An increased Th2 response was described as beneficial in children with COVID-19, due to its potential to reduce exaggerated inflammation ( 49 ). However, we observed that severe COVID-19 patients display strongly up-regulated IL-4 production in both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a report shows that the frequency of Tregs (CD3 + CD4 + CD25 hi CD127 lo ) was significantly declined in critically ill patients, while that was increased in mild and severe cases after SARS-CoV-2 infection [51]. Other studies also found that the proportion of Tregs in CD4 T was reduced in adults and children with severe COVID-19 [11,64,65]. These studies conclude that a reduced number of Tregs, as well as increased Th17 responses, may be attributable to the excessive inflammation and pathogenesis of COVID-19.…”
Section: The Role Of Tregs In the Immunopathology Of Covid-19: Currenmentioning
confidence: 98%
“…Children have a lesser expression of ACE2 receptor in the lungs than adults, and therefore virus has less chance to invade their lungs [35]. Once infected, children develop less intense immunopathological reactions which are probably due to an immature immune system not trained to cause hyperinflammation, and therefore, there is a less chance of developing ARDS [37]. Other supporting factors include better repair power (of damaged respiratory tissues), and low occurrence of comorbid conditions.…”
Section: Low Susceptibility and Severity Of Covid-19 In Childrenmentioning
confidence: 99%